Criteria For Distinction - New Straits Times, (2008)
UNIVERSITY of Malaya is the only excellent tertiary institution in Malaysia. That is according to the Rating System for Malaysian Higher Education 2007 or its Malay acronym (Setara). The findings were released recently.